INTEGRATION OF SWIMMING LESSONS WITH ENVIRONMENTAL EDUCATION (Scientific journal of the Fergana State University, 2025)
In modern educational systems, the priority is the development of a personality with not only physical, but also ecological culture. Swimming, as a basic type of physical activity, promotes health and can be used to form environmental awareness. In the conditions of the sports school of the city of Margilan, the integration of swimming lessons with environmental education is becoming an urgent area that contributes to the comprehensive development of students. The aim of the study is to assess the impact of integrating environmental components into swimming lessons on the level of environmental awareness and physical fitness of athletes.